The Relationship between Pandemic Fatigue and COVID-19 Protective Behavior - Megawati, Eka Roina; Wibawa, Naura Fairuz Selma (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2023)
Background: Pandemic fatigue is a fatigue that can occur during a pandemic that can lead to reduced motivation to follow recommended infection prevention and decreased efforts to seek information related to COVID-19. COVID-19 protective behavior plays an important role in breaking the chain of spreading the COVID-19 virus. This study aimed to find the relationship between pandemic fatigue and COVID-19 protective behavior. Methods: This study used an analytical method with a cross-sectional design, using primary data obtained from questionnaires. The respondents of this study were medical students at Universitas Sumatera Utara and were selected using a stratified random sampling method. The obtained data was analyzed using the chi-square test. Result: Most of the subjects are 20 years old and female. The majority of the pandemic fatigue level was moderate (33%) and the COVID-19 protective behavior level was good (34%). This study found there was a relationship between pandemic fatigue and the protective behavior of COVID-19 infection (p-value = 0.022).